Underwater sound generation and characterisation - Tan, Chun Kang (2015)
This report presents the detailed process of design, fabrication and testing of a water tank with frame. The water tank is used in a laboratory to simulate a closed and controlled environment for the laser and hydrophones to detect underwater generated sound while the frame provides support and portability to the water tank. This report will first discuss about the theoretical knowledge of sound wave characteristics, proceeding on to the designing part of the project, where functional analysis, morphological charts and evaluation matrix will be used to aid the design in fitting the requirements. Next, the report will present drawings and detailed calculations involved in the design process of the tank and frame. The tank will be put up for testing in which we fill up the tank and using a underwater speaker to generate sound, while using a Laser Doppler Vibrometry and hydrophone to detect the sound generated. From the results recorded, we draw the conclusion that the water tank is suitable to be used to compare the LDV and hydrophone and provide the initial steps research in this area. Lastly, this report also presents some recommendations for future projects to enhance the research in this area.